Vitamin E Sebagai Antioksidan Terhadap Ketengikan Bungkil Kopra: Vitamin E As An Antioxidant Against Rancidity of Copra Meal - Sedya, Iga Wahyuning; Rinawidiastuti, Rinawidiastuti; Iskandar, Faruq (Jurnal Riset Agribisnis dan Peternakan, 2023)
Oilcake is a form of animal feed that contains high levels of fat, so it quickly becomes rancid during storage. This research aimed to determine the additional levels of Vitamin E as an antioxidant against the rancidity of copra meal. The design used was a completely randomized design (CRD) with the treatment of vitamin E levels with different percentages, namely treatment (0; 0.05; 0.1; 0.15; 0.2 g) and 5 replications. The parameters include air content, amount of peroxide and free fatty acid content. Data were analyzed using the Analysis of Variance (ANOVA) test. If there were differences, the Duncan New Range Test (DMRT) was carried out. The results showed that adding Vitamin E levels to the rancidity of copra meal had no significant effect (P>0.05) on the water content, peroxide value and free fatty acid levels. The air content value of 8.92-9.36 has no real effect. The peroxide value of 1.36-5.26 has no significant effect. The free fatty acid value of 0.36-0.56 has no significant effect. The conclusion shows that all research parameters have no real effect because the addition of Vitamin E cannot prevent the rancidity of copra cake after 30 days of storage.